Structural changes of the retina, erythropoietin concentration in the vitreous body and peripheral blood in streptozotocin-induced diabetic rats in experiment (intermediate result) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Diabetes with its complications is one of the most important medical, social and economic problems of the health care today. According to the data of the WHO about 4 % of the world population suffer from diabetes, and in some countries it amounts up to 15 % and even to 20 % of population.Purpose. To detect the character of structural changes of the retina and erythropoietin concentration in the vitreous body and peripheral blood, in streptozotocin-induced diabetic rats in experiment during the period of one month.Methods. Wistar rats were included in the experiment. Diabetes was modeled by using a single intraperitoneal injection of streptozotocin in the dose of 65 mgper 1 kg of the body weight. All rats were divided into three groups. REpo administration started on the 1 Oth day in the dose of 6 units per 100 g of the body weight three times a week for a month.Results. Subcutaneous REpo administration in the dose of 6 units per 100 g of the body weight three times a week for a month resulted in a significant increase of EPO concentration in the peripheral blood up to 90.2+7.9 and in the vitreous body — up to 545.7+ 17.67 in comparison with intact rats and rats with modeled diabetes. In a month the EPO concentration in the vitreous body increased significantly in streptozotocin-induced diabetic rats receiving REpo subcutaneously comparing with 2 weeks' follow-up. In rats with modeled diabetes the structural changes of the retina were noted, and the changes were more significant in 1 month term in comparison with 2 weeks' term. There was edema of the retina, vacuolar degeneration of the ganglion cells, blood vessel wall destruction, and focal hemor¬rhages. In the retina of diabetic rats receiving rEpo there were no changes mentioned above in 6 cases in 1 month. The changes detected in 4 cases consisted only in mild edema of the ganglion cell cytoplasm. Herewith disorders of their position architectonics and cell polymorphism were not noted. Distribution density of the ganglion cells was not decreased.There were no structural changes of blood vessels of different size located in the inner retinal layers. Key-words: streptozotocin-induced diabetes, recombinant erythr0poietin, diabetic retinopathy.
Keywords: streptozotocin-induced diabetes; recombinant erythropoietin; diabetic retinopathy